PENGARUH LEVERAGE, KOMPENSASI RUGI FISKAL DAN MANAJEMEN LABA TERHADAP PENGHINDARAN PAJAK - Ridwan - Pajriyansyah; Amrie - Firmansyah (Universitas Pamulang, 2017)
AbstractThis research is aimed to provide empirical evident about relationship between leverage, loss carry forward and earnings management on tax avoidance. Using purposive sampling this research selected 264 firms that are listed in Indonesian Stock Exchange from 2013-2015 as samples. The result of multiple regression of panel data shows that there is significant relationship between leverage and earnings management on tax avoidance. Meanwhile, loss carry forward shows no significant relationship on tax avoidance. Keywords: leverage, loss carry forward, earnings management, tax avoidance